Oxford school atlas for pakistan (new edition) - Khan, dr fazle kareem (Oxford University Press; Malaysia, 2013)
Maps, illustrations, and text describe various aspects of countries of the world including physical features, population, standards of living, natural resources, industries, environmental issues, and climate